Surimi and surimi seafood (CRC Press, 2014)
"Surimi and surimi seafood products were originated in Japan several hundred years ago, and their modern production technology has been professionally documented since the 1950s. The book covers the basic science of surimi (fish proteins) and contains updates on fisheries and the market. It reviews a wide range of surimi seafood manufacturing technologies. It discusses quality assessment/quality control, development, and nutrition technology"--